The selection of case studies: strategies and their applications to IS implementation case studies - Shakir, Maha (Massey University, 2002)
Case study research by definition is well suited to the study of IS implementation, especially when context is important. Furthermore, its products are highly relevant and therefore they appeal to IS practitioners, an audience for which the IS literature has been critiqued of ignoring. While the value of single case research is methodologically viable in the study of critical cases, the multiple case study approach is believed to be more appropriate to the study of typical cases of IS implementations. However, the IS literature provides little guidance on strategies for case study selection, particularly for multiple case studies. More important, is the need to provide the rational for case selection that relates these suggested strategies to the particular objectives of the case research inquiry. The purpose of this study is to fill this gap by providing a review of strategies for single and multiple case study selection in the context of systems implementation. Furthermore, the application of these guidelines in a multiple case study of strategic decision making of enterprise systems implementations will be illustrated.
Keywords: Information system implementation